2022
DOI: 10.3389/fvets.2022.1060140
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary supplementation with quercetagetin on nutrient digestibility, intestinal morphology, immunity, and antioxidant capacity of broilers

Abstract: Quercetagetin (QG) is gaining increased attention as a potential alternative to in-feed antioxidants due to its antioxidant activity. This experiment was conducted to investigate the effects of dietary supplementation with QG on nutrient digestibility, intestinal morphology, immunity, and antioxidant capacity of broilers. Four hundred 1-day-old Ross 308 broilers were randomly assigned into 4 groups with 10 replicates in each group and 10 broilers in each replicate. The four dietary treatments included the basa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 29 publications
3
4
0
Order By: Relevance
“…In this study, there were no significant differences in ADG, ADFI, F/G, and the liver, kidney, and spleen organ indexes among the rabbits across the three groups, implying that the dosage and time of ZEN and QG administration had no significant effect on the growth performance of rabbits, including their liver, kidney, and spleen development. This is partially consistent with a previous report where QG (3.2, 4.8, or 6.4 mg/kg, fed for 42 days) had no significant effect on the spleen, thymus, and bursa of fabricius organ indexes in broilers ( Wu et al, 2022b ). ZEN effects on growth performance are related to dosage, exposure time, animal species, growth stage, and other factors ( Gajęcka et al, 2016 ; Chen et al, 2019 ; Liu et al, 2020 ; Ropejko and Twarużek, 2021 ).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…In this study, there were no significant differences in ADG, ADFI, F/G, and the liver, kidney, and spleen organ indexes among the rabbits across the three groups, implying that the dosage and time of ZEN and QG administration had no significant effect on the growth performance of rabbits, including their liver, kidney, and spleen development. This is partially consistent with a previous report where QG (3.2, 4.8, or 6.4 mg/kg, fed for 42 days) had no significant effect on the spleen, thymus, and bursa of fabricius organ indexes in broilers ( Wu et al, 2022b ). ZEN effects on growth performance are related to dosage, exposure time, animal species, growth stage, and other factors ( Gajęcka et al, 2016 ; Chen et al, 2019 ; Liu et al, 2020 ; Ropejko and Twarużek, 2021 ).…”
Section: Discussionsupporting
confidence: 93%
“…Notably, QG (6.4 mg/kg, fed for 42 days) significantly increased the blood GSH-Px activity and the liver GSH-Px, and SOD activities in broilers. At the same time, QG significantly reduces the MDA level, which is partially consistent with the results in this study ( Wu et al, 2022b ). Besides, QG supplementation significantly reduced the abundance of Keap1 mRNA in the liver of rabbits in the ZEN + QG group compared to the ZEN group.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…However, previous research has demonstrated that active components of TCE, such as flavonoids and phenolic acids, may boost Ig levels and improve animal immune function [ 43 , 73 ]. Dietary quercetagetin increased blood IgG levels, according to Wu et al [ 74 ], who identified the flavonol compound chemically. The levels of IgM and IgA in serum were higher in broiler chickens fed diets supplemented with 1 or 2 g/kg Acanthopanax polysaccharides, according to Long et al [ 75 ].…”
Section: Discussionmentioning
confidence: 99%